Oxygen reduction reaction of different electrodes in dimethyl sulfoxide solvent for Li-air batteries. (14th September 2015) - Duan, Donghong; You, Xiu; Ren, Wenjun; Wei, Huikai; Liu, Huihong; Liu, Shibin
Abstract: The α-MnO2 nanorod catalysts are prepared by chemical precipitation method, the morphology and crystal configuration are evaluated by X-ray diffraction (XRD) and scanning electron microscopy (SEM). In the electrolyte salt such as tetrabutylammonium perchlorate/dimethyl sulfoxide (TBAClO4 /DMSO) and Lithium bis (trifluoromethanesulfonyl) imide/dimethyl sulfoxide (LiTFSI/DMSO), the reaction mechanism and the products of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) process on glassy carbon electrode, Au electrode and α-MnO2 electrode are analyzed by cyclic voltammetry. In addition electrochemical quartz crystal microbalance (EQCM) are used to measure the mass change on electrode in cyclic voltammetry scan. In LiTFSI/DMSO system, the results show that the ORR reaction mechanism, species and distribution of products on different electrodes are not exactly identical, α-MnO2 nanorod catalysts have good catalytic activity and greatly enhance the reaction kinetics of ORR and OER process. Highlights: The reaction mechanism and the products of ORR process are analyzed. EQCM is used to measure the mass change on electrode surfaces. α-MnO2 nanorod catalysts have good catalytic activity and greatly enhance the reaction kinetics of ORR and OER process.